Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.ebscohost.com/login.aspx?direct=true&db=bri&AN=111289127&site=ehost-live&scope=site KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2015.1092466 10/gfv5xz 2129771:L2HUHYLN 2339240:24LHAF5C 2339240:K9R22K2F 2339240:WV3XY5NW 2405685:6ZLKKKH7 2405685:8V49PM4G 2405685:KILQYYBU 2405685:SXKPQUJ5 2534378:6TMRG3EP 2534378:BF6PBW3F 2534378:QQ6BVI89
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

Recommendation 7: Use ICT to provide access to content, professional development and professional learning communities - Lawrie, J.; Hennessy, Sara; Haßler, Björn; Phalachandra; Lawrie, J. (Where it's needed most: Quality professional development for all teachers, 2015)
EdTechHub.Source: 2129771:KQGAREE9 EdTechHub.Source: 2129771:KQGAREE9 KerkoCite.ItemAlsoKnownAs: 2129771:KQGAREE9 2405685:PKLI25VA
Keywords: C:Fragile contexts; dode_eth-src-dode; dode_eth-trf2-dode